2021
DOI: 10.1159/000515627
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Blood Purification in Moderate and Severe COVID-19 Patients: A Prospective Cohort Study

Abstract: <b><i>Introduction:</i></b> Coronavirus disease 2019 (COVID-19) is characterized by hyperinflammation and coagulopathy. Severe cases often develop respiratory distress, requiring mechanical ventilation and with critical cases progressing to acute respiratory distress syndrome. Control of hyperinflammation has been proposed as a possible therapeutic avenue for COVID-19; extracorporeal blood purification (EBP) modalities offer an attractive mean to ameliorate maladaptive inflammation. Wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…With the aid of blood purification, the excess fluid could be efficiently eliminated to achieve negative volume balance. Consistently, current studies have also indicated the application of the absorbing filter Oxiris in moderate or severe or critically-ill COVID-19 patients with acute respiratory distress syndrome (ARDS), CSS or secondary infections (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 78%
“…With the aid of blood purification, the excess fluid could be efficiently eliminated to achieve negative volume balance. Consistently, current studies have also indicated the application of the absorbing filter Oxiris in moderate or severe or critically-ill COVID-19 patients with acute respiratory distress syndrome (ARDS), CSS or secondary infections (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 78%
“…However, there is still insufficient evidence on the optimum timing and indication for initiation of CRRT with oXiris filter in order to achieve the best outcome. 8 Furthermore, the high cost of CRRT with such filters and its limited availability may limit its usage. In addition, the need for insertion of haemodialysis catheters into central veins prior to commencement of CRRT, carry the risks of pneumothorax, bleeding and catheter-related sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Other sorbents, assembled in special filters or cartridges, are currently used for the treatment of sepsis (oXiris, CytoSorb, etc. ), although robust evidence in this field is still lacking for most long-term outcomes (e.g., 90-day mortality rate) [ 43 , 44 ].…”
Section: Extracorporeal Organ Supportmentioning
confidence: 99%